An Illustrative Consideration of the Uncanny - Quy, Maximillian (Auckland University of Technology, 2016)
Lights Out / The Box is a collection of short comics situated within the horror/mystery genres. My thesis and exegesis explore the challenges of conveying horror in the comics medium, with a specific focus on eliciting a particular atmosphere, sense of mystery and the uncanny, through the combination of illustration, text and design.
Keywords: Graphic novel; Illustration; Uncanny; Short story; Horror; Mystery; Sequential art